Open Science, Open Data, Open Source - Vos, Rutger A. (2017)
Making research findings available free of charge for all readers has been a major challenge identified by the European Commission. Several initiatives have been made to facilitate scientific data to the community. But has science progresses, the volume of data and platforms where information can be found also increases. The task of searching for data can be overwhelming. Pedro Fernandes, IGC member and Coordinator of the GTPB - the Gulbenkian Training Programme in Bioinformatics, and Rutger Vos, from Naturalis Biodiversity Center, set to tackle this problem by creating useful information to help producing, storing, managing and finding scientific information in open resources. Their efforts resulted in 'Open Science, Open Data, Open Source - 21st century research skills for the life sciences', an e-book that can be freely used by the scientific community, policy-makers, funding agencies, among others.